Procesy neologizacji we współczesnej frazeologii rosyjskiej i słowiańskiej . - Walter, Harry (Przegląd Rusycystyczny, 2008)
PROCESSES OF NEOLOGIZATION IN RUSSIAN AND SLAVONIC PHRASEOLOGY Summary The article intends to present a comprehensive survey of the development of phraseology in Russian and other Slavonic languages. Unfortunately, most of the dictionaries of neolo-gisms do not contain phraseology. On the one hand, we observe a lack of reliable reference works and dictionaries of phraseological neologisms, refl ecting the active development of phraseology in contemporary Slavonic languages. On the other hand we observe the intensive research in this fi eld because phraseology plays an important role in the development of those languages. It is intended to analyze the interaction between phraseological structures and further idiomatic units, for example proverbs and winged words, to try to compile com-prehensive dictionaries, which illustrate the rapid development of Slavonic phraseological systems. Emphasizing the inadequacy of historical end etymological research of Russian and Slavonic phraseology, the author lines out possibilities for further research by regarding the results of synchronic and diachronic analysis of phraseology and proposes a comprehensive bibliography of reference works on the topic of phraseology in Slavonic languages. PROCESY NEOLOGIZACJI WE WSPÓŁCZESNEJ FRAZEOLOGIIROSYJSKIEJ I SŁOWIAŃSKIEJ Streszczenie Artykuł stanowi próbę spojrzenia na rozwój frazeologii rosyjskiej i innych języków sło-wiańskich. Niestety, większość słowników neologizmów nie zawiera frazeologii. Z jednej strony mamy do czynienia z brakiem rzetelnych prac na temat neologiki frazeologicznej i słowników odzwierciedlających aktywny rozwój frazeologii języków słowiańskich. Z drugiej strony obserwujemy intensywne badania tej sfery, ponieważ frazeologia gra ważną rolę w rozwoju tych języków. Autor próbuje zanalizować relacje między różnymi rodzajami związków frazeologicznych i im podobnych zjawisk językowych (takich jak przysłowia czy skrzydlate słowa), mając na względzie potrzebę opracowania słownika mogącego zilustrować szybki rozwój słowiańskich systemów frazeologicznych. Podkreślając niewystarczalność historycznych i etymologicznych badań nad frazeologią rosyjską i słowiańską, autor ukazuje możliwości dalszych badań z wykorzystaniem rezultatów synchronicznych i diachronicznych badań frazeologii, proponując równocześnie stworzenie bibliografi i prac poświęconych frazeologii języków słowiańskich.